The Peru Urban versus Rural Asthma (PURA) Study: methods and baseline quality control data from a cross-sectional investigation into the prevalence, severity, genetics, immunology and environmental factors affecting asthma in adolescence in Peru. Issue 1 (22nd February 2012) - Robinson, Colin L; Baumann, Lauren M; Gilman, Robert H; Romero, Karina; Combe, Juan Manuel; Cabrera, Lilia; Hansel, Nadia N; Barnes, Kathleen; Gonzalvez, Guillermo; Wise, Robert A; Breysse, Patrick N; Checkley, William
Abstract : Objectives: According to a large-scale international survey, Peru has one of the highest prevalences of asthma worldwide; however, data from this survey were limited to participants from urban Lima. The authors sought to characterise the epidemiology of asthma in Peru in two regions with disparate degrees of urbanisation. In this manuscript, the authors summarise the study design and implementation. Design: A cross-sectional study. Participants: Using census data of 13–15-year-old adolescents from two communities in Peru, the authors invited a random sample of participants in Lima (n=725) and all adolescents in Tumbes (n=716) to participate in our study. Primary and secondary outcome measures: The authors asked participants to complete a questionnaire on asthma symptoms, environmental exposures and socio-demographics and to undergo spirometry before and after bronchodilator, skin allergy testing and exhaled nitric oxide testing. The authors obtained blood samples for haematocrit, total IgE levels, vitamin D levels and DNA in all participants and measured indoor particulate matter concentrations for 48 h in a random subset of 70–100 households at each site. Results: Of 1851 eligible participants, 1441 (78%) were enrolled and 1159 (80% of enrolled) completed all physical tests. 1283 (89%) performed spirometry according to standard guidelines, of which 86% of prebronchodilator tests and 92% of postbronchodilator tests were acceptable and reproducible. 92% of allergy skin tests had an adequate negative control. The authors collected blood from 1146 participants (79%) and saliva samples from 148 participants (9%). Overall amounts of DNA obtained from blood or saliva were 25.8 μg, with a 260/280 ratio of 1.86. Conclusions: This study will contribute to the characterisation of a variety of risk factors for asthma, including urbanisation, total IgE levels, vitamin D levels and candidate genes, in a resource-poor setting. The authors present data to support high quality of survey, allergic, spirometric and genetic data collected in our study.